ABOUT AN ALGORITHM OF OPTIMIZATION OF THE INGOT CRYSTALLIZATION PROCESS - A. N. Chichko; V. A. Matochkin; A. V. Demin; O. I. Chichko; V. F. Sobolev (Литьë и металлургия)
The model of the regimes optimization of secondary cooling MNLZ, differing from the known ones by taking into account pressures and deformations occurring in different zones of ZVO is offered. The model takes into account the thermal and physical characteristics of steel type at evaluation of the heat exchange coefficient.